THE IMPACT OF MANPOWER EDUCATION AND GOVERNMENT EXPENDITURE ON EDUCATION SECTOR ON ECONOMIC GROWTH OF LABUHANBATU REGENCY - Zulpan Akhir Ritonga; Imam Mukhlis (Quantitative Economics Journal, 2020)
This study is based on the fact that education contributes greatly to economic growth through the improvement of knowledge, skills, attitudes and productivity, so that education is expected to produce quality workforce. This study aims to determine how the impact of education level achieved by the workforce. The level of education achieved by the workforce is distinguished between primary, secondary, and tertiary education. It also aims to find out how the impact of government spending on government education sector on economic growth in Labuhanbatu District during the period of 2002-2015. Data analysis method used in this research is descriptive method, completed by analysis with econometric data analysis with multiple regression model based on production function Y = f (K, L). Regression analysis was performed using Ordinary Least Square (OLS) method. The model used is the model of endogenous economic growth (new growth model). This study uses secondary data obtained from the publication of survey results related to the Statistic Indonesia with time series 2002-2015. Data analysis using multiple linear regression with the help of statistical test of E-view 6.0 application program. The results of this study indicate that all the independent variables have a positive and significant impact on economic growth in Labuhanbatu regency. Estimation results for economic growth obtained R2 of 0.994414. This means that as much as 99.4414 percent of economic growth variables can be explained by the variables of primary school educated workers, high school educated workers, college educated labor, human development index, and government spending in the education sector while the remaining 0, 5586 percent is explained by other variables outside the model. In the end, the variables of elementary school educated labor, high school educated labor, college educated labor, human development index, and government expenditure in the education sector are expected to increase economic activity in order to achieve economic growth and improve the welfare of the community.